Method for increasing solid content of polymer emulsion
By adding a concentrated agent solution to the polymer emulsion and leaving it stand, the problem of difficult to remove the reaction heat and aggregate when increasing the concentration of the polymer emulsion is improved, safe and simple solid content is improved, and drying costs are reduced.
Patent Information
- Application Number
- CN202411850198.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process of polymer emulsion, increasing the material concentration will make it difficult to remove the reaction heat, resulting in out-of-control and accompanied by problems such as copolymerization and agglomeration. The prior art is difficult to effectively solve these problems.
By adding a concentrated agent solution to the polymer emulsion and mixing evenly while standing, the solid content of the polymer emulsion is increased, heating and continuous stirring are avoided, and the operation is simple and safe, and the stability of the emulsion will not be damaged.
It is achieved without changing the stability and product performance of the polymer emulsion, thereby increasing the solid content of the polymer emulsion, reducing drying costs, and avoiding the problems of out-of-control reactions and aggregates.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, and in particular to a method for increasing the solid content of a polymer emulsion. Background Art
[0002] Polymer emulsions are generally polymerized by emulsion method, seed emulsion method, microsuspension method, and seed microsuspension method. The concentration of the material in the polymerization process determines the concentration of the final emulsion product. The increase in the concentration of the material in the polymerization process will increase the heat release per unit volume of the polymerization process, which will make it difficult to remove the reaction heat and even lead to problems such as loss of control of the polymerization process. At the same time, increasing the polymer concentration in the reaction process will increase the number of material particles per unit volume and the probability of expansion between particles, which will lead to problems such as aggregation and agglomeration.
[0003] In order to solve the above problems caused by increasing the material concentration, polymerization engineering generally increases the heat transfer area inside the reactor, such as adding an internal cooling tube, but the internal cooling tube may have cleaning dead corners or internal leakage that is difficult to detect, leading to more serious product problems; or designing a jacket heat transfer on the stirring rod or stirring blade, this type of stirring is also prone to internal leakage and thus causing serious production accidents; or using a continuous tubular reaction, but this type of reactor is used to produce polymer emulsions due to the fast flow rate, which may cause demulsification, pipe blockage, and difficulty in cleaning. There is also a method of extracting part of the water by heating the polymer emulsion under vacuum or non-vacuum after the polymerization is completed, in order to achieve the purpose of increasing the solid content of the polymer emulsion, but the polymer emulsion will have problems such as easy surface crusting and slag formation and high energy consumption during secondary heating. Summary of the invention
[0004] In view of the above deficiencies in the prior art, the present invention provides a method for increasing the solid content of a polymer emulsion. The present invention can evenly mix a concentrate solution with a polymer emulsion without heating or continuous stirring, and increase the solid content of the polymer emulsion in a static state, without spending a lot of money on formula, process and device modifications in the polymer emulsion synthesis stage. The method provided by the present invention is simple to operate, safe in the process, and will not destroy the stability of the polymer emulsion or affect the performance of the polymer product, which is of great significance for reducing the drying cost of the polymer emulsion.
[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0006] In a first aspect, the present invention provides a method for increasing the solid content of a polymer emulsion, comprising the following steps: stirring and mixing a concentrate solution and a polymer emulsion, allowing the mixture to stand, sampling and testing the solid content as required during the standing process, stopping the standing when the solid content reaches an expected value, and draining the upper layer of clear water to obtain a polymer emulsion with increased solid content;
[0007] Wherein, the concentrator is one or more monovalent and divalent alkali metal salts.
[0008] Furthermore, the added amount of the concentrator is 100-10000 ppm of the effective content of the polymer emulsion.
[0009] Furthermore, the added amount of the concentrator is 1000-5000 ppm of the effective content of the polymer emulsion.
[0010] Furthermore, the mass concentration of the concentrate solution is 0.5% to 8%.
[0011] Furthermore, the mass concentration of the concentrate solution is 1% to 5%.
[0012] Furthermore, the alkali metal salt includes but is not limited to sodium chloride, potassium chloride, calcium chloride, sodium alginate, and potassium alginate.
[0013] Furthermore, the alkali metal salt is sodium alginate.
[0014] Furthermore, the solid content testing method during the static process includes but is not limited to a heating and baking self-constant weight method and a near infrared method.
[0015] Furthermore, a solid content-time variation curve is drawn based on the solid content data obtained from the standing process test, which is used to determine the standing time for the same type of polymer emulsion to reach the target solid content.
[0016] Furthermore, during the stirring and mixing process, the mixing temperature is controlled according to the storage environment and temperature requirements of the polymer emulsion.
[0017] Furthermore, the polymer emulsion is an emulsion obtained by co-polymerization of one or more processes of emulsion polymerization, seed emulsion polymerization, microsuspension polymerization, and seed microsuspension polymerization, or is a composite of polymer emulsions prepared by different processes.
[0018] Furthermore, the method for increasing the solid content of the polymer emulsion specifically comprises the following steps:
[0019] (1) Obtaining the initial solid content of the polymer emulsion;
[0020] (2) Calculate the effective content in the polymer emulsion based on the initial solid content of the polymer emulsion a , calculate the amount of concentrate added based on a b ;
[0021] (3) Add the concentrate solution into the polymer emulsion and stir to mix evenly;
[0022] (4) Allow to stand, during which time take samples to test the solid content as needed;
[0023] (5) After the solid content reaches the expected value, the mixture is allowed to stand for a while, and the upper layer of clear water is discharged to obtain a polymer emulsion with an increased solid content (i.e., a concentrated polymer emulsion).
[0024] Furthermore, the effective content a The calculation method is as follows:
[0025]
[0026] Furthermore, the amount of the concentrate added is b The calculation method is as follows:
[0027]
[0028] in, i The ratio of the amount of concentrate added to the effective content of the polymer emulsion is 100 ppm ≤ i ≤10000 ppm.
[0029] In a second aspect, the present invention provides a polymer emulsion with increased solid content obtained by treatment using the method.
[0030] In a third aspect, the present invention provides a device for implementing the method for increasing the solid content of a polymer emulsion, the device comprising a concentrating tank, the material temperature in the concentrating tank being controlled by a jacket, the concentrating tank being provided with a drainage device, the drainage device being a water pump, or the drainage device being a plurality of direct discharge valves or direct discharge ports arranged from the upper part to the top of the concentrating tank.
[0031] Compared with the prior art, the present invention is beneficial in that:
[0032] The invention provides a method for improving the solid content of a polymer emulsion. The invention adds a concentrator solution to the polymer emulsion without heating or continuous stirring, and concentrates the polymer emulsion in a static state after uniform mixing, thereby improving the solid content of the polymer emulsion. The method does not require a large amount of modification of formula, process and device in the polymer emulsion synthesis stage, is simple to operate, has a safe process, will not destroy the stability of the polymer emulsion, and will not affect the performance of the polymer product, and is of great significance to reducing the drying cost of the polymer emulsion. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The invention provides a method for improving the solid content of a polymer emulsion, comprising the following steps: stirring and mixing a concentrate solution with a polymer emulsion, allowing the mixture to stand, sampling and testing the solid content as required during the standing process, stopping the standing when the solid content reaches an expected value, and draining the upper layer of clear water to obtain a polymer emulsion with improved solid content; wherein the concentrate is one or more monovalent and divalent alkali metal salts.
[0035] In some examples, the amount of the concentrator added is 100-10000 ppm of the effective content of the polymer emulsion.
[0036] In some examples, the mass concentration of the concentrate solution is 0.5% to 8%.
[0037] In some examples, the alkali metal salt includes, but is not limited to, sodium chloride, potassium chloride, calcium chloride, sodium alginate, and potassium alginate.
[0038] In some examples, the solid content testing method during the static process includes, but is not limited to, a heating and baking self-constant weight method and a near infrared method.
[0039] In some examples, the polymer emulsion is an emulsion obtained by co-polymerization of one or more processes of emulsion polymerization, seed emulsion polymerization, microsuspension polymerization, and seed microsuspension polymerization, or is a compound of polymer emulsions prepared by different processes.
[0040] Example 1
[0041] A polymer emulsion with increased solid content
[0042] Add 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry is 3060 g); start the stirring speed at 600 rpm, add 15.3 g of 2% sodium alginate aqueous solution (the amount of sodium alginate is 0.306 g, which is 100 ppm of the effective content of the polyvinyl chloride paste resin slurry), stir for 10 min and then stop stirring, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper clear liquid with a peristaltic pump to obtain a polyvinyl chloride paste resin slurry with increased solid content. The obtained slurry was dried by spray drying to prepare paste resin powder. The drying inlet air temperature was 170 °C and the outlet air temperature was 55 °C. The obtained paste resin powder was prepared into standard paste according to GB / T12004.2-1996 "Preparation of polyvinyl chloride paste resin paste", and the paste viscosity was tested according to GB / T 12004.4-2003 "Determination of apparent viscosity of polyvinyl chloride plasticized paste Brookfield test method". The test results are shown in Table 2.
[0043] Example 2
[0044] A polymer emulsion with increased solid content
[0045] Add 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry is 3060 g); start the stirring speed at 600 rpm, add 306 g of 2% sodium alginate aqueous solution (the amount of sodium alginate is 6.12 g, which is 2000 ppm of the effective content of the polyvinyl chloride paste resin slurry), stir for 10 min and then stop stirring, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper layer of clear water with a peristaltic pump to obtain a polyvinyl chloride paste resin slurry with increased solid content.
[0046] Example 3
[0047] A polymer emulsion with increased solid content
[0048] Add 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry is 3060 g); start the stirring speed at 600 rpm, add 612 g of 2% sodium alginate aqueous solution (the amount of sodium alginate is 12.24 g, which is 4000 ppm of the effective content in the polyvinyl chloride paste resin slurry), stir for 10 min and then stop stirring, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper layer of clear water with a peristaltic pump to obtain a polyvinyl chloride paste resin slurry with increased solid content.
[0049] Example 4
[0050] A polymer emulsion with increased solid content
[0051] Add 9000 g of vinyl chloride-vinyl acetate copolymer emulsion prepared by emulsion process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the vinyl chloride-vinyl acetate copolymer emulsion is 3060 g); start the stirring speed at 600 rpm, add 306 g of 2% sodium alginate aqueous solution (the amount of sodium alginate is 6.12 g, which is 2000 ppm of the effective content of the vinyl chloride-vinyl acetate copolymer emulsion), stop stirring after stirring for 10 min, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper clear night with a peristaltic pump to obtain a vinyl chloride-vinyl acetate copolymer emulsion with increased solid content.
[0052] Example 5
[0053] A polymer emulsion with increased solid content
[0054] Add 9000g of ethylene-vinyl acetate copolymer emulsion prepared by emulsion process with an initial solid content of 51% to a 10 L stirring concentration tank (the effective content in vinyl chloride-vinyl acetate copolymer emulsion is 4590g); start the stirring speed at 600 rpm, add 459g of 2% sodium alginate aqueous solution (the amount of sodium alginate is 9.18g, which is 2000ppm of the effective content of vinyl chloride-vinyl acetate copolymer emulsion), stop stirring after stirring for 10 minutes, let it stand for 24 hours, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper clear night with a peristaltic pump to obtain a vinyl chloride-vinyl acetate copolymer emulsion with increased solid content.
[0055] Example 6
[0056] A polymer emulsion with increased solid content
[0057] Add 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry is 3060 g); start the stirring speed at 600 rpm, add 6.12 g of 5% sodium alginate aqueous solution (the amount of sodium alginate is 0.306 g, which is 100 ppm of the effective content of the polyvinyl chloride paste resin slurry), stir for 10 min and then stop stirring, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper clear liquid with a peristaltic pump to obtain a polyvinyl chloride paste resin slurry with increased solid content.
[0058] Example 7
[0059] A polymer emulsion with increased solid content
[0060] Add 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry is 3060 g); start the stirring speed at 600 rpm, add 3.825 g of 8% sodium alginate aqueous solution (the amount of sodium alginate is 0.306 g, which is 100 ppm of the effective content of the polyvinyl chloride paste resin slurry), stir for 10 min and then stop stirring, let it stand for 24 h, take the lower layer of emulsion during the standing process, and test the solid content, particle size, viscosity, and mechanical stability according to GB / T 11175-002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. Stop standing when the solid content reaches the expected value, and pump out the upper clear liquid with a peristaltic pump to obtain a polyvinyl chloride paste resin slurry with increased solid content.
[0061] Comparative Example 1
[0062] 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% was added to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry was 3060 g); the stirring speed was started at 600 rpm, 15.3 g of pure water was added, and the stirring was stopped after stirring for 10 min, and the mixture was allowed to stand for 24 h. During the standing period, the lower layer of emulsion was taken out and the solid content, particle size, viscosity and mechanical stability were tested according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1. The obtained slurry was dried by spray drying to prepare paste resin powder. The drying inlet air temperature was 170°C and the outlet air temperature was 55°C. The obtained resin powder was prepared into standard paste according to GB / T12004.2-1996 "Preparation of polyvinyl chloride paste resin paste", and the paste viscosity was tested according to GB / T12004.4-2003 "Determination of apparent viscosity of polyvinyl chloride plasticized paste Brookfield test method". The test results are shown in Table 2.
[0063] Comparative Example 2
[0064] 9000 g of polyvinyl chloride paste resin slurry prepared by microsuspension process with an initial solid content of 34% was added to a 10 L stirring concentrating tank (the effective content in the polyvinyl chloride paste resin slurry was 3060 g); the stirring speed was started at 600 rpm, 0.306 g of sodium alginate powder was added, and the stirring was stopped after stirring for 10 min. The mixture was allowed to stand for 24 h. During the standing period, the lower layer of emulsion was taken out and the solid content, particle size, viscosity and mechanical stability were tested according to GB / T 11175-2002 "Test Methods for Synthetic Resin Emulsions". The test results are shown in Table 1.
[0065] Table 1: Test results of solid content (TSC), particle size, viscosity and mechanical stability
[0066]
[0067] As shown in Table 1, after adding the concentrate solution to the polymer emulsion and mixing it evenly, the solid content of the polymer emulsion first continued to rise and then tended to stabilize during the standing process; after standing for 24 hours, as the solid content of the polymer emulsion increased, its corresponding viscosity increased, while the particle size and mechanical stability of the polymer emulsion did not change significantly. However, simply adding water to the polymer emulsion and standing it did not achieve the effect of increasing the solid content; increasing the mass concentration of the concentrate solution, due to the long dispersion time of the concentrate solution, the concentration speed decreased, and the particle size of the concentrated emulsion increased slightly, and was still within the normal range; the inventors found that if the mass concentration of the added concentrate solution was too high, it would cause an abnormal increase in the particle size of the concentrated polymer emulsion; adding solid powder of alkali metal salt to the polymer emulsion, the solid content of the polymer emulsion was increased while accompanied by local demulsification.
[0068] Table 2: Effect of increasing solid content on paste viscosity
[0069]
[0070] As can be seen from Table 2, after the concentrated polymer emulsion (Example 1) and the unconcentrated polymer emulsion (Comparative Example 1) were spray-dried into resin powder, the viscosity of the resin pastes was not changed, indicating that the concentration followed by spray drying by the method of the present invention will not affect the final product and can also reduce the cost of spray drying.
[0071] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for increasing the solid content of a polymer emulsion, characterized in that: The method comprises the following steps: stirring and mixing a concentrate solution and a polymer emulsion, allowing the mixture to stand, sampling and testing the solid content as required during the standing process, stopping the standing when the solid content reaches an expected value, discharging the upper clear water, and obtaining a polymer emulsion with increased solid content; wherein the concentrate is one or more monovalent or divalent alkali metal salts.
2. A method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: The added amount of the concentrator is 100-10000 ppm of the effective content of the polymer emulsion.
3. The method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: The mass concentration of the concentrate solution is 0.5% to 8%.
4. The method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: The alkali metal salts include, but are not limited to, sodium chloride, potassium chloride, calcium chloride, sodium alginate, and potassium alginate.
5. A method for increasing the solid content of a polymer emulsion according to claim 4, characterized in that: The alkali metal salt is sodium alginate.
6. The method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: The solid content testing method during the static process includes, but is not limited to, a heating and baking self-constant weight method and a near infrared method.
7. The method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: A solid content-time variation curve is drawn based on the solid content data obtained from the standing process test, which is used to determine the standing time for the same type of polymer emulsion to reach the target solid content.
8. The method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: During the stirring and mixing process, the mixing temperature is controlled according to the storage environment and temperature requirements of the polymer emulsion.
9. A polymer emulsion with increased solid content obtained by treatment with the method according to any one of claims 1 to 8.
10. A device for implementing the method for increasing the solid content of a polymer emulsion according to claim 1, characterized in that: The invention comprises a concentration tank, wherein the material temperature in the concentration tank is controlled by a jacket, and the concentration tank is provided with a drainage device, wherein the drainage device is a water pump, or the drainage device is a plurality of direct discharge valves or direct discharge ports arranged from the upper part to the top of the concentration tank.
Citation Information
Patent Citations
Latex and preparation method thereof
CN103772717A
Polymer emulsoid concentrating method
CN1406987A